Human knowledge and human nature : a new introduction to an ancient debate - Carruthers, Peter, 1952- (Oxford [England] ; New York : Oxford University Press, 1992)
Contemporary debates in epistemology devote much attention to the nature of knowledge, but neglect the question of its sources. The distinctive focus of Human Knowledge and Human Nature is on the latter, especially on the question of innateness. Peter Carruthers's aim is to transform and reinvigorate contemporary empiricism, while also providing an introduction to a range of issues in the theory of knowledge. He gives a lively presentation and assessment of the claims of classical empiricism, particularly its denial of substantive a priori knowledge and also of innate knowledge. He argues that we would be right to reject the substantive a priori but not innateness, and then presents a novel account of the main motivation behind empiricism, which leaves contemporary empiricists free to accept innate knowledge and concepts. He closes with a discussion of scepticism, arguing that acceptance of innate concepts may lead to a decisive resolution of the problem in favour of realism. The book will be of equal interest to students of the history of modern philosophy and the theory of knowledge, and their teachers. It provides a new way of looking at classical empiricism, and should lead to a renewal of interest in the innateness issue in epistemology
1. Introduction: Modes of Knowledge -- 2. Knowledge out of Reason: Platonism -- 3. The Empiricist Case against Platonism -- 4. The Empiricist Case against Nativism -- 5. Is Innate Knowledge even Possible? -- 6. The Case for Innate Mental Structure -- 7. The Case for Innate Concepts -- 8. The Case for Innate Knowledge -- 9. Powers of Mind: The Core of Empiricism -- 10. Evolutionary Nativism and A Priori Knowledge -- 11. Our Knowledge of the External World -- 12. Knowledge by Best Explanation
Includes bibliographical references (pages 195-196) and index
Keywords: Knowledge, Theory of; Innate ideas (Philosophy); Empiricism